2016
DOI: 10.1021/acs.joc.5b02524
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Tetrahydrofurans via Catalytic Asymmetric [3 + 2] Cycloaddition of Heterosubstituted Alkenes with Oxiranes

Abstract: An efficient diastereo- and enantioselective [3 + 2] cycloaddition of heterosubstituted alkenes with oxiranes via selective C-C bond cleavage of epoxides has been developed. The reaction was catalyzed by a chiral N,N'-dioxide/Ni(II) catalyst, and a variety of chiral highly substituted tetrahydrofurans were obtained in up to 99% yield, 92/8 dr, and 99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Oxiranes have become interesting precursors in the last few years. Yuan et al [102] demonstrated an efficient diastereo- and enantioselective [3 + 2] cycloaddition of heterosubstituted alkenes with oxiranes via selective C−C bond cleavage of epoxides to give chiral THFs (Scheme 12). The reaction was catalyzed by a chiral N,N ′-dioxide/Ni(II) catalyst which was derived from L-ramipril (Ra) by complexing with Ni(BF 4 ) 2 ·6H 2 O.…”
Section: Tetrahydrofuransmentioning
confidence: 99%
“…Oxiranes have become interesting precursors in the last few years. Yuan et al [102] demonstrated an efficient diastereo- and enantioselective [3 + 2] cycloaddition of heterosubstituted alkenes with oxiranes via selective C−C bond cleavage of epoxides to give chiral THFs (Scheme 12). The reaction was catalyzed by a chiral N,N ′-dioxide/Ni(II) catalyst which was derived from L-ramipril (Ra) by complexing with Ni(BF 4 ) 2 ·6H 2 O.…”
Section: Tetrahydrofuransmentioning
confidence: 99%
“…Specifically, it was proposed that 1,5-dienes 1 derived from alkylidenemalononitrile and a cis-buten-1,4-diol derivative could undergo polythermal transformation involving Cope rearrangement, Boc-deprotection, and intramolecular oxy-Michael addition. Reviews of furan synthesis literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and "domino reactions [38,39] " in general reveal that this proposal is unique and would access novel trisubstituted THFs. The most relevant prior art is summarized in Scheme 1, which demonstrates the likelihood of oxy-Michael additions to alkylidenemalonic acid derivatives.…”
Section: We Have Been Advancing the Classic Cope Rearrangementmentioning
confidence: 99%
“…Considering the relevance of tetrahydrofurans to drug discovery, a variety of strategies have been developed to access them in efficient ways. [13] Synthesis strategies fall into one of two subcategories: (a) constructive synthesis, where the THF scaffold is assembled [14][15][16][17][18][19][20][21][22][23] or (b) by an approach that functionalizes a preexisting THF core (e.g C-H functionalization, cross-coupling reactions. [24][25][26][27][28][29][30][31] The former category is of particular relevance to this report.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Cyclopropanes were for al ong time considered as rather kinetically inert species due to the absence of highly polarized bonds in the all-carbon ring. [7] On the other hand, three-membered heterocycles can exhibit ar eactivity of synthetic equivalents of common 1,3dipoles (azomethine ylides for aziridines, [8] carbonyl ylides for oxiranes, [9] synthon II in Scheme 1a)p roducing cycloadducts in reactions with the appropriate unsaturated compounds. [7] On the other hand, three-membered heterocycles can exhibit ar eactivity of synthetic equivalents of common 1,3dipoles (azomethine ylides for aziridines, [8] carbonyl ylides for oxiranes, [9] synthon II in Scheme 1a)p roducing cycloadducts in reactions with the appropriate unsaturated compounds.…”
mentioning
confidence: 99%